The Islamic Perspectives of Freedom, Veiling, and Open Mindedness: A Current Misunderstand Elements - Hussain, Abrar; Marghoob Ahmad (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Islam is the oldest divine religion with a complete code of life. Islam, being natural, comprehensive, rational, and authentic, provides its followers, the Muslims, with a comprehensive set of rules, guidelines, and criteria to follow. Due to its rapid prevalence, currently, 1.8 billion people around the world follow Islamic principles. Because of the vast expansion of Muslim populations, some elements are presently understood and followed wrongly. The Islamic teaching of personal freedoms, particular individual choices like veiling and social interactions, is often misunderstood as being impressed by the modern world. Freedom, a widely used term in current debates, is frequently used to express one’s power and depress or impose on others. Likewise, the concept of veiling is typically regarded as a personal choice, though it is mandatory in Islam. Every man and woman is ordered to follow the Islamic principle of veiling, which not only gives protection but also gives satisfaction and peace of mind and is a symbol of a true follower of Islam. Additionally, the concept of an open mind is growing rapidly, and every individual is trying to avoid the other’s actions and moments to show his open mindness. Among others, the children-parent relationship greatly helps to properly understand these misunderstood elements. Through a comprehensive review of theological sources and modern interpretations, this paper aims to contribute to a more balanced understanding of these elements and their place in Islamic thought today.